2009
DOI: 10.5012/bkcs.2009.30.12.2999
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-chromatographic Analysis for HPV-16 and 18 E7 Proteins as a Biomarker of Cervical Cancer Caused by Human Papillomavirus

Abstract: Among the more than 120 different types of human papillomavirus (HPV), types 16 and 18 have been known to be high risk agents that cause cervical cancer. We examined, in an immuno-chromatographic analysis, the potential of using the early gene product, E7 protein, as a diagnostic marker of cervical cancer caused by HPV. We developed monoclonal antibodies specific to HPV-16 and 18 E7 proteins that were produced from bacterial cells using gene recombinant technology. For each E7 protein, the optimal antibody pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…As known, E6 and E7 transforming proteins are consistently expressed in HPV life cycle [3941]. Several studies have shown the induction of antibody responses against E6 and E7 oncoproteins in patients with cervical cancer higher than in healthy subjects [39, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…As known, E6 and E7 transforming proteins are consistently expressed in HPV life cycle [3941]. Several studies have shown the induction of antibody responses against E6 and E7 oncoproteins in patients with cervical cancer higher than in healthy subjects [39, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Protein E6 dihitung menggunakan metode Bicinchoninic Acid (BCA). Langkah tersebut diulang untuk menghasilkan antigen protein E6 HPV-18 hingga didapatkan keseluruhan protein rekombinan yang dibutuhkan (Yetisen et al, 2013;Kim et al, 2009). Untuk mendapatkan antibodi monoklonal digunakan mencit sebagai hewan coba.…”
Section: Konstruksiunclassified
“…Pada test line di NC membrane diletakkan antibodi yang telah disiapkan sebanyak 1 μL. Antibodi protein E6 HPV-16 diletakkan pada T1 dan antibodi protein E6 HPV-18 pada T2 (Kim et al, 2009). Control line mengandung antibodi spesifik terhadap konjugat partikel emas.…”
Section: Konstruksiunclassified